2021
DOI: 10.3171/2020.3.jns193230
|View full text |Cite
|
Sign up to set email alerts
|

The microenvironment in sporadic and neurofibromatosis type II–related vestibular schwannoma: the same tumor or different? A comparative imaging and neuropathology study

Abstract: OBJECTIVEInflammation and angiogenesis may play a role in the growth of sporadic and neurofibromatosis type 2 (NF2)–related vestibular schwannoma (VS). The similarities in microvascular and inflammatory microenvironment have not been investigated. The authors sought to compare the tumor microenvironment (TME) in sporadic and NF2-related VSs using a combined imaging and tissue analysis approach.METHODSDiffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 44 publications
3
55
1
Order By: Relevance
“…On the contrary, when the infiltration of lymphocyte and macrophage marker expression was taken together as an inflammatory score, a higher score was associated with slower tumor growth. This is in direct contradiction to the current literature that suggests that immune cell infiltration leads to faster tumor growth [ 6 , 8 , 17 ]. However, our study is the largest so far in regard to the description of immune cell infiltration and volumetric growth.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, when the infiltration of lymphocyte and macrophage marker expression was taken together as an inflammatory score, a higher score was associated with slower tumor growth. This is in direct contradiction to the current literature that suggests that immune cell infiltration leads to faster tumor growth [ 6 , 8 , 17 ]. However, our study is the largest so far in regard to the description of immune cell infiltration and volumetric growth.…”
Section: Discussioncontrasting
confidence: 92%
“…Based on the current literature, the observation of decreased tumor growth with increased inflammatory infiltration was unexpected. Until now, the contrary has been advocated, that immune cell infiltration may be an expression of tumor-associated macrophages driving schwannoma growth [ 6 , 8 , 17 ]. Only one study that assessed PET imaging with specific tracers for inflammation in a small group of vestibular schwannomas shown a higher cell density in non-growing tumors compared to growing VS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo studies in sporadic VS have demonstrated that kinetic parameter estimates derived through use of the ETM with low‐spatial, HT resolution DCE‐MRI accurately reflect inter‐tumor differences in tissue vascularity metrics and correlate with differences in macrophage content and tumor growth rate 5,30 . However, the inherent low‐spatial resolution in derived parameter maps limited accurate assessment of intratumoral heterogeneity, especially within smaller lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The ETM has been adopted in this study as previous application of this model with low‐spatial resolution HT data sets derived from DTR DCE‐MRI was found to give both tissue‐validated and clinically relevant kinetic parameter estimates 4,5,30 . Recent studies have also shown through a model selection process using the Akaike information criteria, that the ETM was one of the optimal models in pharmacokinetic analysis of DCE‐MRI data in brain tumors 42 and papillary thyroid carcinoma 43 .…”
Section: Discussionmentioning
confidence: 99%
“…5H). Recent studies of schwannomas highlight the presence and clinical influence of macrophages, which can be important paracrine sources of both HGF and PDGF 12,59 . Thus, Nf2-deficiency may also enable macropinocytic scavenging in response to paracrine factors from the microenvironment, which could further drive schwannoma heterogeneity by activating additional signaling pathways.…”
Section: Nf2 -/-Scs Develop Autocrine Heterogeneitymentioning
confidence: 99%